Evaluation of the potential of Pinus greggii wood for pulp production (Revista de Ciências Agroveterinárias, 2022)
The long fiber paper production segment in Brazil is restrict on the use of only two species of the Pinus genus (P. taeda and P. elliottii), therefore, it is essential to evaluate new species, aiming to expand the alternatives for this segment. In this sense, the present study aimed to evaluate the physical, chemical and anatomical properties of Pinus greggii wood aiming at the pulp production. For this, three 7-year-old trees were used, from which disks were removed along the stem. These were used to evaluate physical (average and weighted basic density), chemical (ash, extractive, lignin and holocellulose) and anatomical (tracheid dimensions and anatomical indicators) properties. According to the physical characterization, an average value of basic density of 0.346 g.cm-3 and weighted of 0.343 g.cm-3 was obtained, which allows classifying it as light or low density. Regarding the chemical composition, the species showed high levels of lignin and extractives (34.83% and 6.25%, respectively) and low levels of holocellulose (58.92%) and ash (0.20%). For the tracheids dimensions, mean values of 2.31 mm in length, 41.30 µm in width, 34.81 µm in lumen diameter, and 3.25 µm in cell wall thickness were obtained. As for the results of the quality index, the species stood out for the wall fraction (15.96%), flexibility coefficient (84.31%), Runkel index (0.19) and felting index (55.15). In general, the P. greggii wood presents potential for the pulp production, standing out for its anatomical indicators and for the tracheids dimensions, which are similar to the values found for P. taeda at the same age. However, it has high levels of lignin and extractives, which can increase the consumption of reagents and decrease the yield of the pulping process, which needs to be proven in studies on this topic.
Keywords: physical characterization; quality indicators; chemical composition; long fiber cellulose